Evaluation of adverse effect of second line ART in PL HIV patients treated by second line ART - Singh, Narendra; Kumar, Lalit; Singh, Desh Nidhi (International Journal of Advances in Medicine, 2020)
Background: AIDS was first recognized in USA Subject whose viral load was very high more than 5000 copy and CD4 count remain below 100 for 6 months and decrease 50% of base line call as ART failure. There are grade 1, 2, 3 and 4 adverse effect can be seen .in treating of PL. HIV by ART2. Methods: It was Single centre hospital based clinic pathological study and continuous longitudinal, prospective and retrospective , observational, in ART PLUS Centre considering of all patient on 1st line ART who are screened for treatment failure based on clinical, immunological and virological criterias as decided by SACEP from 2016 to 2018. Results: This study shows increase in serum bilirubin from 5 to 13 in study subject and there was increase in no from 4 to 5 in subject of less than 9 Haemoglobin and in the group of 9 to 10 level Haemoglobin of subjects no. increase from 4 to 5 but more than 10 subject decrease from 110 to 108. Subject increase 6 to 10 of serum creatinine level >1.5mg /dl., This shows second line ART have adverse effect on liver , kidney and hematology. There is some adverse effect is seen as nausea, vomiting, headache, skin rash, abdominal pain and muscle pain, there was some serious adverse effect that required hospitalization. Conclusions: Study show that ART2 have adverse effect on liver and kidney function and anaemia. Some general adverse effect seen that also required treatment.